Two Reasons Why the Future of the City May Teach Us Something Key: Abstracting and Being Wise - Simona Chiodo (Rivista di Estetica)
We may think of the city as a kind of symbol of what most characterises our era: if it is true that our era is most characterised by complexity and uncertainty, it is also true that the city may be what can most clearly show what complexity and uncertainty actually mean. Our era’s harshest lesson is precisely that, when we move from the village to the city, specifically contemporary cities becoming not only exponentially big but also exponentially interconnected, complexity and uncertainty increase as our era’s equally harsh global challenges, from climate change to pandemics to wars. Yet, contemporary cities’ global challenges may be not only harsh lessons but also unmissable opportunities. In what follows, as a philosopher, I shall work on at least two reasons why contemporary cities, specifically their future as what is likely to further increase complexity and uncertainty, may teach us something key from an epistemological perspective: first, to abstract more and, second, to be wiser, which are two epistemological capabilities that may be more crucial than ever in the future.